(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
The purpose of this paper is threefold. First, it aims to explain the political background of the 2019 parliamentary elections in Ukraine and the profile of the parties represented in the Verkhovna Rada (Ukrainian Parliament). Second, it intends to analyse the role of European integration in the political agenda of the Ukrainian Parliament in the years 2019-2022 (before the beginning of Russia’s full-scale invasion of Ukraine) and the nature of EU-Ukrainian relations in the said period. Finally, the article investigates the consolidating potential of European integration among different political actors in the Ukrainian Parliament after February 2022. By doing so, we will try to assess whether Russia’s military aggression has triggered the Ukrainian Parliament to unify efforts in adopting legislation on the democratisation of Ukraine